The significance of emotions in women with endometriosis and their challenges with infertility / Norashikin Mohd Mokhtar, Irma Ahmad and Mohd Faiz Ismail - Mohd Mokhtar, Norashikin; Ahmad, Irma; Ismail, Mohd Faiz (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
Endometriosis is a standing and distressing condition that leads to notable physical discomfort, like pelvic pain and fertility issues and has deep emotional impacts on those affected by it (Giudice & Kao in 2004). The extended wait for diagnosis that can span about 7 to 9 years worldwide only adds to the mental strain on patients (Frankel, in 2022). Studies have shown that endometriosis can have an effect on women’s health and relationships as well as their overall quality of life. According to research findings women with endometriosis tend to experience issues than those, without the condition, which adds to their emotional struggles (Aerts et al., 2018).The possibility of infertility linked to endometriosis also contributes to feelings of anxiety, depression and a sense of losing control over their ability to conceive.